ANZTLA Newsletter Author and Subject Indexes - Canty, Val; Davis, Wendy; Hocking, Rosemary (ANZTLA EJournal, 2014)
These indexes refer to the 61 volumes of the printed ANZTLA newsletter. Val Canty compiled the lists up to volume 51. Rosemary Hocking and Wendy Davis completed the indexing of the remanding volumes.